(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
The comprehensive reforms carried out in the country’s education system are aimed at ensuring a high level of education quality, and one of the key success factors in this area is the modernization of the management and teaching staff of educational institutions the acquisition of knowledge, skills and abilities, as well as innovative electronic didactic teaching aids and scientific research textbooks.